Broun, Edwin. Edwin Broun to Bettie Broun, Petersburg VA, April 21, 1863 - Broun, Edwin (Valdosta, Georgia: Valdosta State University Archives and Special Collections, 2020., 1863)
Easton April 21, 1863 Dear Daughter, Notwithstanding it has only been a few days since I wrote you a letter. I will again. Thinking you will be glad even to [receive?] a note from home.
Handwritten letter from Edwin Broun to his daughter Bettie Broun. Easton Place, Virginia. April 21, 1863. 2 page[s]. Edwin Broun writes his daughter Bettie at the Womans College in Petersburg, Virginia. Topics include weather, farming, and family.
Keywords: Personal correspondence; American Civil War (1861-1865); Broun, Edwin, 1819-1904; Broun, Bettie Lee, 1846-1927; Women College Students; Virginia--Heathsville; Virginia--Petersburg; Letters